PEMBENTUKAN KARAKTER ANTI KORUPSI PADA SANTRI DI PONDOK MODERN DAARUL ABROR KACE - Ndaru Satrio; Heru Siswanto (Abdi Bhara, 2022)
The socialization of the law with the theme of Anti-Corruption Character Building found that the participants, inthis case the Daarul Abror Islamic boarding school students, didnot fully know about anti-corruption. The positive impacts of theimplementation of this legal socialization include: (1) knowingthe attitude that is the driving element of anti- corruptionbehavior; (2) know the principles of anti-corruption behavior;(3) knowing the problems that may arise in eradicatingcorruption, so that the community in general and students inparticular can prevent this from happening. The methods usedare: (1) explaining attitudes which are the driving elements ofanti-corruption behavior; (2) Explaining the principles of anticorruptionbehavior; (3) explain the important elements in anticorruptioneducation; (4) The socialization of the law is carriedout in the form of in-depth interactive lectures and discussions atPondok Modern Daarul Abror Kace. The above was done faceto-face at the Daarul Abror Kace Modern Pondok Mosque. Theindicator that we use to measure the success of this outreach is aquestionnaire that we distribute to participants before thisactivity is carried out and immediately after this event.